(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the assistance of the nursing team regarding the prevention and treatment of inpatients with Pressure Injury in Intensive Care Units. This article is a systematic review of the literature with meta synthesis, which accompanies the PRISMA protocol for the search and use of studies, of which 22 articles were part of the construction of the study. The survey of scientific productions occurred between the months of August 2020 and September 2020. It was observed before the study the difficulties that nurses find in care within an ICU, from the quality of care provided, the difficulty of implementing the protocols of the unit and even the lack of professional qualification. It is necessary to have a higher qualification of the professionals, and a greater attention to patients in critical condition of the ICU, so that the nurse can act correctly, providing assistance in a qualified way.